PENYULUHAN BUDIDAYA TANAMAN HIDROPONIK DI DESA KALENSARI KECAMATAN WIDASARI KABUPATEN INDRAMAYU - Henly Yulina (universitas wiralodra, 2019)
Community consumption needs are not only basic needs such as rice, corn, wheat, and cassava. But also need vegetables and fruits to complement the body's nutritional needs. The development of vegetable commodities in quantity and quality is faced with the narrowing of agricultural land. Hydroponics is a method of farming that does not use soil media and can use narrow or less productive lands such as home yards.Counseling and training have been programmed in Kalensari Village, Widasari Subdistrict, Indramayu Regency with the target of PKK women’s. This counseling provides new knowledge for participants to be able to optimize their home yards so that they can be beneficial both in terms of aesthetics and even in the future in terms of the economy. But there are obstacles in the feedback of material because there are still many participants who cannot speak Indonesian well and correctly. Key words: cultivation, hydroponics, kalensari village